International migration in Asia and the Pacific determinants and role of economic integration - Aiko Kikkawa; Raymond Gaspar; Cyn-Young Park (Asian Development Bank (ADB), 2019)
International migration is an essential element of economic integration. Yet, the intraregional movement of people and labor in Asia and the Pacific has stagnated in recent years even as the flow of goods, services, and investment have steadily risen. This paper examines key factors driving the movement of people from and within the region using bilateral international migrant stock data. Our analysis shows that commonly known determinants such as income differences; population size; and political, geographical, and cultural proximities between the migrant source and destination countries are associated with greater movement, along with the growing share of older population in destination economies and the similarities in the level of educational attainment. The paper also finds that crossborder migration is affected, in varied directions, by the degree of economic integration between the source and destination economies, especially through bilateral trade and value chain links. The offshoring of production - and hence jobs and other economic opportunities - to migrant source countries suppresses outmigration, but the expected rise in the source country income will eventually promote migration by relaxing financial constraints.
Keywords: F22; O15; 330; international migration; labor mobility; regional economic integration